174 ANALYSIS OF ANTIBIOTIC ADMINISTRATION IN A NEONATAL INTENSIVE CARE UNIT: ROUTINE CARE CANNOT BE PRESUMED TO BE "OPTIMAL!". (1st January 2005) - Harden, J.; Buchter, S.; Clark, P.; Sola, A.
Abstract : Background: A prolonged period from the time of order to actual administration of antibiotics (ATB) is associated with worse outcome in cases of systemic infection. Several factors are involved in this lag time. Detection of a few isolated cases, with a period > 2 hours at GMH NICU, prompted implementation of a process for quality improvement (PQI). Objective: To evaluate the time period between ATB orders and administration in the NICU and the possible effects of PQI on such a period. Methods: Over a twelve-day period, we collected data prospectively to identify the total period between order and initiation of administration of ATB. These included time of written order and time of administration and time of the several "intermediate" steps involved in getting the ATB to the patient (order to computer scan time, order entry time, medication tube system time and others). To improve the ATB administration time, we established a collaborative PQI of communication and education by a multidisciplinary committee of pharmacy, nursing, and medical staff. After the PQI, we randomly collected the same data prospectively for ten new admissions over a 30-day period. We compared the total time and the time of each step between the two periods. Results: Before the PQI, the turnaround time was on average 135 minutes, with a median time of 115 minutes. After the PQI was fully implemented, the total time to ATB administration decreased to 37 minutes on average, with a median time of 32 minutes. The lag time between orders written to orders scanned was reduced from an average 61 minutes and median 57 minutes to 12 minutes on average with a median of 9 minutes. In the pharmacy, the time also decreased significantly (median of 6 minutes to 1.5 minutes), as was the time the medications were sent by tube from the pharmacy to administration of ATB (49 minutes to 32 minutes). Conclusion: The time from order of ATB to administration was too long at GMH NICU and a PQI was effective for achieving significantly shorter times. We speculate that frequent NICU therapies, such as this one, will reveal opportunity for improvement if carefully analyzed through collaborative efforts at any institution.